Extracting Innovative Buyers by Scoring Using Innovator Theory - Iwata, Ryo; Kuramoto, Kaoru; Matsumoto, Kenyuu; Kumagai, Satoshi (International Review of Management and Marketing, 2020)
For companies that want to sell a high volume of products, it is important to identify innovative buyers to help with product marketing efforts. The purpose of this paper is to construct a model extracting whether users are innovative buyers or not from their purchase histories at physical stores and from access logs from an online-to-offline (O2O) site. Innovative buyers are users who influence other users' product purchases, also known in innovator theory as innovators and early adopters. They purchase products quickly, visiting physical stores such as supermarkets and convenience stores. In other words, innovative buyers are known to have high cosmopolite natures. In extracting innovative buyers, we estimated the speed of user product purchases and their cosmopolite natures. This estimation index can also be referred to as innovator scores. We went on to verify this method with socioeconomic status points, personality points and communication points (SPC points), using consciousness data and profile data collected from a panel on an O2O site. Thus, we showed that innovative buyers could be extracted using this new method, and the accuracy was higher than that of traditional methods measuring only the speed from product sale start to user purchase. Keywords: Innovator Scores, Innovative Buyers, SPC Points, O2O, Cosmopolite Natures, Extraction Model JEL Classifications: M31, O39, C38 DOI: https://doi.org/10.32479/irmm.9815